COMPANY SIZE AS A MODERATING VARIABLE ON ENTERPRISE RISK MANAGEMENT DISCLOSURE OF BANKING COMPANIES IN INDONESIA (Jurnal Dinamika Akuntansi, 2022)
Purpose: This research aims to review the relationship of the board of commissioners, the ownership concentration, the audit committee meetings, and the risk management committee with enterprise risk management disclosure moderated by the company size.Method: The population for this study was 46 banking companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The sample selection was carried out using the purposive sampling technique which resulted in 39 companies with 117 analytical units performed using documentation techniques. Data were analyzed using moderating regression analysis based on Ordinary Least Square (OLS).Findings: The outcome of this research showed that the board of commissioners and audit committee meetings had a positive effect on the enterprise risk management disclosure while the ownership concentration and risk management committee did not affect the enterprise risk management disclosure. The company size can moderate the influence of the board of commissioners and audit committee meetings but is not able to moderate the influence of the ownership concentration and risk management committee. The findings prove companies that have a good board of commissioners and a competent audit committee can trigger companies to disclose enterprise risk management broadly.Novelty: This study adds company size as moderating variable. Based on the investment concept, namely high-risk high return, and low-risk low return. When the company wants to get big returns, the company will face big risks as well. This is directly proportional to companies with large sizes. The bigger company so the higher the risks faced by the company. This is also related to the disclosure of the risks.